2021
DOI: 10.1101/2021.04.02.21254771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative SARS-CoV-2 viral-load curves in paired saliva and nasal swabs inform appropriate respiratory sampling site and analytical test sensitivity required for earliest viral detection

Abstract: Early detection of SARS-CoV-2 infection is critical to reduce asymptomatic and pre-symptomatic spread of COVID-19, curb the spread of viral variants by travelers, and maximize efficacy of therapeutic treatments. We designed a study to evaluate the preferred test sensitivity and sample type (saliva and nasal swab) for detecting early infections of COVID-19. We performed a case-ascertained study to monitor household contacts of individuals recently diagnosed with a SARS-CoV-2 infection. From those individuals, w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 74 publications
4
30
0
Order By: Relevance
“…Saliva in comparison, can be reliably self-collected, reducing the burden on healthcare workers and arrives in a format that can readily be pooled [ 6 , 7 , 12 ]. Furthermore, a recent study demonstrated that SAR-CoV-2 was detected in saliva using RT-PCR 1.5–4.5 days before the viral load could be detected in a paired nasal swab [13] , which may explain how an independent group observed a higher efficiency of detecting asymptomatic infected individuals using saliva pooling (pool size of up to 12) when compared to nasal swabbing methods [14] . Although there are many publications discussing pooling, most of these studies consist of predictive modeling, proof-of-concept testing protocols and strategic analyses [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Saliva in comparison, can be reliably self-collected, reducing the burden on healthcare workers and arrives in a format that can readily be pooled [ 6 , 7 , 12 ]. Furthermore, a recent study demonstrated that SAR-CoV-2 was detected in saliva using RT-PCR 1.5–4.5 days before the viral load could be detected in a paired nasal swab [13] , which may explain how an independent group observed a higher efficiency of detecting asymptomatic infected individuals using saliva pooling (pool size of up to 12) when compared to nasal swabbing methods [14] . Although there are many publications discussing pooling, most of these studies consist of predictive modeling, proof-of-concept testing protocols and strategic analyses [ 12 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a recent study from Huang et al demonstrated higher RNA expression of the ACE2 receptor and the TMPRSS2 internalization protease in epithelial cells of the glands and oral mucosae, which translated into a higher salivary viral burden [ 17 ]. Moreover, recent evidence provided by Savela et al suggests that high-sensitivity saliva-based tests can detect the presence of SARS-CoV-2 earlier in the infection when compared to self-collected anterior-nares nasal swabs [ 18 ].…”
Section: What Specimen To Collectmentioning
confidence: 99%
“…Compared to the gold standard nasopharyngeal swab, testing saliva for SARS-CoV-2 has been shown to have at least equal, and sometimes higher, sensitivity for detecting asymptomatic carriers (Savela et al, 2021 ; Yokota et al, 2021 ). Recent meta-analyses comparing the efficiency of PCR detection when applied to nasopharyngeal and saliva samples (Butler-Laporte et al, 2021 ; Cañete et al, 2021 ; Khiabani and Amirzade-Iranaq, 2021 ; Lee et al, 2021 ; Moreira et al, 2021 ), confirm the high specificity of saliva, with sensitivity positively correlating with stage of infection (i.e., early) and sampling technique (Tan et al, 2021 ).…”
Section: Saliva For Sars-cov-2 Infection Diagnosismentioning
confidence: 99%
“…Studies have demonstrated that SARS-CoV-2 RNA can appear in saliva 24–48 h prior to detection by nasopharyngeal swabs (Wyllie et al, 2020 ; Borghi et al, 2021 ), and 1.5–4.5 days prior to detection by anterior nasal swabs (Savela et al, 2021 ). In line with this, evidence also suggests that viral replication in the oral cavity may precede that within the nasopharynx, with multiple oral cells susceptible to SARS-CoV-2 infection (Huang et al, 2021 ).…”
Section: Saliva For Sars-cov-2 Infection Diagnosismentioning
confidence: 99%